Efficiency of War Crimes Proceedings Before Serbian Courts - Kolaković-Bojović, Milica (Zbornik Instituta za kriminološka i sociološka istraživanja, 2015)
Two decades after the war conflicts within the ex-Yugoslav territory, there is still an issue of the length of war crimes criminal proceedings, as well as the issue of the investigation of other war crimes that haven’t been proceeded with. A long time after the war is more complicated to discover, investigate and prosecute war crimes. Evidence is placed all over the region and is difficult to access. A huge problem is the lack of data on war crimes cases statistics, which should be an indicator of efficiency, as well as a basis for further case management and human/material resources planning. An additional problem lies in the extensive case material due to numerous accused, victims and witnesses. Parallel work on a huge number of extensive cases causes chronic overload of existing administrative and material capacities. Bearing all that in mind, there is a need for an analytical and strategic approach to the domestic war crime proceedings aimed at improving their efficiency.